Assessing Vaccination Status of First-Time College Students at the University of Wisconsin-La Crosse - Larsen, Alexandra A. (My University, 2019)
Vaccination is one of the great public health achievements of the twentieth century. Yet infectious disease outbreaks continue to pose a risk to the public, necessitating sustained action focused on vaccination efforts. The college population is at particular risk for infectious disease due to frequent close contact with large groups. The purpose of this study was to establish the response rate of first-time college students in the University of Wisconsin-La Crosse fall 2018 cohort to the vaccination records request from the campus student health center. Using secondary data from student health records, vaccination status for the hepatitis B, HPV, MMR, meningitis serogroups ACWY, Tdap, and varicella vaccines were also assessed. Additionally, vaccination rates and response to records request were compared based on respondents' sex, race/ethnicity, and home state. Results indicated a 66% response rate to the vaccination records request. Vaccination rates were strong among responding students with the exceptions of the HPV and meningitis ACWY vaccines. Results were significant for a relationship between sex and HPV vaccination status. Female students were more strongly represented among students with completed HPV vaccine series. Educational and outreach efforts to improve vaccination rates should particularly focus on the HPV vaccine, especially for male students.
Keywords: Vaccination -- Wisconsin -- La Crosse; College students -- Wisconsin -- La Crosse; Public health -- Wisconsin -- La Crosse